Real exchange rates in Nigeria : a preliminary study - Obadan, Michael I.; National Centre for Economic Management and Administration (NCEMA) (Ibadan, Nigeria : National Centre for Economic Management and Administration, 1994)
Provides alternative measures of bilateral real exchange rate, and nominal and real effective exchange rate indices in Nigeria.
Includes bibliographical references (p. [75]-76)
oif 23/10/15
Loan
Keywords: Foreign exchange rates